2012
DOI: 10.1128/jvi.01725-12
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the M-Gene Segment Can Substantially Increase Replication Efficiency of NS1 Deletion Influenza A Virus in MDCK Cells

Abstract: bInfluenza viruses unable to express NS1 protein (delNS1) replicate poorly and induce large amounts of interferon (IFN). They are therefore considered candidate viruses for live-attenuated influenza vaccines. Their attenuated replication is generally assumed to result from the inability to counter the antiviral host response, as delNS1 viruses replicate efficiently in Vero cells, which lack IFN expression. In this study, delNS1 virus was parallel passaged on IFN-competent MDCK cells, which resulted in two stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…It has been suggested that the viral polymerase complex is involved in regulation of M2 mRNA splicing regulation through interaction with the splice site in exon 2 and other studies have also argued that viral polymerases have a role in this process444748. Evidence from our own and other studies have suggested a mechanism involving NS1 in the regulation of splicing of M mRNAs, as the M2/M1 mRNA ratio is altered in viruses lacking the NS1 protein94449. However, it is less clear how expression of the spliced form of NS mRNA is regulated to influence NEP expression.…”
Section: Discussionmentioning
confidence: 67%
“…It has been suggested that the viral polymerase complex is involved in regulation of M2 mRNA splicing regulation through interaction with the splice site in exon 2 and other studies have also argued that viral polymerases have a role in this process444748. Evidence from our own and other studies have suggested a mechanism involving NS1 in the regulation of splicing of M mRNAs, as the M2/M1 mRNA ratio is altered in viruses lacking the NS1 protein94449. However, it is less clear how expression of the spliced form of NS mRNA is regulated to influence NEP expression.…”
Section: Discussionmentioning
confidence: 67%
“…Experiment using guinea pigs demonstrated that strains without pH1N1 M could not transmit the virus while those containing NL + M + NA + HA had great transmission even with a 100 PFU virus dose (Campbell et al 2014). According to van Wielink and colleagues (2012), mutations in M and NP indicated an average decrease in virus titers when combined while mutations in M itself increased virus titer indicating that M alone determined enhanced replication. NS1 is expressed at high levels after infection and facilitates virus replication (Hale et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…2014). According to van Wielink et al . (2012), combined mutations in M and NP lead to an average decrease in virus titer, whereas mutations in M itself increase the virus titer, indicating that M alone determines enhanced replication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations